2005
DOI: 10.1097/01.psy.0000188479.04891.74
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled Trial of a Selective Serotonin Reuptake Inhibitor in the Treatment of Nondepressed Tinnitus Subjects

Abstract: These results suggest that the majority of individuals in this study did not benefit from paroxetine in a consistent fashion. Further work remains to be done to determine if subgroups of patients (e.g., those who tolerate higher doses, those who are depressed) may benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 39 publications
(30 reference statements)
0
70
1
2
Order By: Relevance
“…SSRI treatment has also been shown to be effective in treating both tinnitus and depression 44 . Most notably, the use of SSRI's in non-depressed tinnitus patients has not shown any benefit, further illustrating the interconnected relationship between tinnitus and depression 45 . Effective non-medical options also exist, most notable cognitive behavioral therapy (CBT).…”
Section: Resultsmentioning
confidence: 99%
“…SSRI treatment has also been shown to be effective in treating both tinnitus and depression 44 . Most notably, the use of SSRI's in non-depressed tinnitus patients has not shown any benefit, further illustrating the interconnected relationship between tinnitus and depression 45 . Effective non-medical options also exist, most notable cognitive behavioral therapy (CBT).…”
Section: Resultsmentioning
confidence: 99%
“…The most recent Cochrane review included 4 trials of tricyclic antidepressants, 1 trial of trazodone, and 1 trial of a selective serotonin reuptake inhibitor (paroxetine). 170,171,[180][181][182][183][184] Of these trials, 4 are double blind, 1 is single blind, and 1 does not clearly state blinding. Three of the tricyclic antidepressant trials showed modest improvement of tinnitus, but the treatment effects may have been related to modulation of depression and anxiety rather than any change in character or intensity of tinnitus.…”
Section: Antidepressantsmentioning
confidence: 99%
“…36 Whereas the review identified 6 studies that favored treatment over control for tinnitusspecific QOL outcomes [169][170][171][172][173][174] and 5 studies that favored treatment over control for subjective tinnitus loudness outcomes, 169,[173][174][175][176] selection and other bias, small sample sizes, and imprecise effect estimates led to an assessment of low or insufficient strength of evidence for these outcomes.…”
Section: Supporting Textmentioning
confidence: 99%
See 1 more Smart Citation
“…If a combination of treatments designed to improve mood is effective in that regard, it cannot be too surprising that the degree of distress in connection with tinnitus experience is diminished also. There is certainly no basis from the literature for a proposal that distressing tinnitus absent psychological problems such as depression and anxiety will be effectively managed by use of antidepressants (Robinson et al, 2005).…”
Section: Forms Of Treatmentmentioning
confidence: 99%